Knowing to Ask and Feeling Safe to Tell - Understanding the Influences of HCP-Patient Interactions in Cancer Care for LGBTQ+ Children and Young People - Gannon, Tamsin; Phillips, Bob; Saunders, Daniel; Berner, Alison May (Frontiers in Oncology, 2022)
Background: Lesbian, gay, bisexual, transgender, queer or questioning (LGBTQ+) people experience healthcare inequalities in cancer care. Previous studies have focused on knowledge, attitudes and behaviours of healthcare professionals (HCPs) treating adults with cancer and how these contribute to inequalities. To date, no research has focused on HCPs treating LGBTQ+ children and adolescents with cancer in the UK. This is important given that this group may be at a critical time for exploring their gender identity and sexual orientation, whole also facing a cancer diagnosis. We aimed to explore the knowledge, attitudes and behaviours of paediatric, teenage and young adult oncology HCPs treating LGBTQ+ patients in the UK. Methods: We carried out semi-structed interviews with 8 HCPs in paediatric, teenage and young adult (TYA) oncology from the Royal Marsden Hospitals NHS Trust. Eight questions were asked, centred around participants' knowledge, attitudes and behaviours regarding management of LGBTQ+ patients in oncology. Interview transcripts were analysed by inductive thematic analysis. Results: We identified 10 themes, including novel themes (how HCPs acquire knowledge and expectations of a ‘third party’ to be the expert) which may underlie previously observed trends in knowledge, attitudes and behaviours of HCPs. We highlight other themes and HCP concerns specific to care of LGBTQ+ patients in paediatrics (influence of the parental-carer dynamic, concerns around patient age and development as a barrier to disclosure) which require further research. We found evidence of the interrelatedness of HCP knowledge, attitudes and behaviours and the ability of these elements to positively influence each other. We mapped our themes across these elements to form a new suggested framework for improving HCP-patient interactions in LGBTQ+ Cancer Care. We found a need both for individual HCP education and organisational change, with creation of a culture of psychological safety to improve patient care. Conclusion: Knowledge, attitudes and behaviours of HCPs are closely interdependent when providing care to young LGBTQ+ patients with cancer. The authors suggest that future efforts to improve care of these patients address this complexity by spanning the domains of our suggested framework. Whilst HCP education is essential, change must also occur at an organisational level.